2011
DOI: 10.2528/pier11051709
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Microstrip Mixer Based on Graphene

Abstract: Abstract-In this work, a millimeter wave microstrip frequency-mixer design based on graphene is presented. The desired frequency mixing behavior is obtained using a nonlinear component consisting in a microstrip line gap covered by a graphene layer. The circuit includes microstrip filters that have been designed to obtain a high isolation between the input and output ports. The nonlinear behavior of the frequency mixer has been experimentally evaluated in the 38.6-40 GHz input signal frequency range, for diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
(20 reference statements)
1
40
0
Order By: Relevance
“…Millimeter-wave and submillimeter-wave frequency multipliers [1][2][3][4][5][6] and mixers [7][8][9][10][11][12][13][14] based on planar Schottky diodes are widely used for atmosphere and space detection. The multipliers are usually driven by an oscillator [15][16][17][18] or a phase-locked millimeter-wave source.…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter-wave and submillimeter-wave frequency multipliers [1][2][3][4][5][6] and mixers [7][8][9][10][11][12][13][14] based on planar Schottky diodes are widely used for atmosphere and space detection. The multipliers are usually driven by an oscillator [15][16][17][18] or a phase-locked millimeter-wave source.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinearity of graphene has been studied extensively and verified experimentally to be widely used in many applications including harmonic generation, frequency mixers, optical rectification, amplifiers and many other nonlinear devices [18,19]. Generally, the nonlinear effect occurs when a material responds in a not linearly proportional way to the interacted incident radiation field.…”
Section: Model Of Graphenementioning
confidence: 99%
“…This results from the linear dispersion of the carriers in graphene, instead of the parabolic dispersion of conventional semiconductors. Some works have reported demonstration of frequency multiplier and mixer at microwave frequency range [14][15][16]. However, no systematic microwave nonlinear property study on graphene has been reported.…”
Section: Introductionmentioning
confidence: 99%